Contribución de los forrajes mejorados a la productividad ganadera en sistemas de doble propósito - Argel M., Pedro J. (2006)
Dual purpose systems represent 78% of the bovine inventory in tropical Latin America and contribute approximately 42% of the fresh milk produced. However, these systems are characterized by low animal productivity due mainly to the use of low quality, poorly managed forages, and to low genetic potential of the animals. During recent decades the Tropical Forages Project of CIAT and national research and development institutions have identified and characterized forage grasses and legumes adapted to wide range of edaphic and climatic conditions that are in a process increasing adoptation and have significantly increased plantings of improved forages in regions of Panama, Mexico and Central America. Increases in animal productivity are estimated as 26% for milk and 6% for beef due exclusively to the adoption of Brachiaria cultivars. More recently, the commercial availability of cv. Mulato, an apomictic hybrid of Brachiaria has resulted in increased milk and beef productivity in dual purpose farms due mainly to high production of good quality forage that permits a higher stocking rate per unit area. Similarly, shrub legumes such as Cratylia argentea can substitute for high cost supplements such as poultry manure during the dry season in dual purpose farms. The perennial peanut (Arachis pintoi) in association with stoloniferous grasses has resulted in productivity increases of 15% milk and 20% beef in experimental plots, with the additional benefit of increasing soil biological activity, notably in the form of higher earthworm populations. It is a demonstrated fact that the utilization of properly managed improved forages not only permits increasing animal productivity, but also reduces soil erosion problems and allows the release of on-farm land not suited for grazing for other uses such as reforestation.